Resource use and management - Elida Brereton (Cambridge Univ, 1992)
The book examines issues related to people's use of natural and human resources. Resources examinated in some detail include water, rubber, gold, drainage basins and areas in national parks. Human resources focus on manufacturing, urban landscape, nuclear energy, waste disposal, pollution and dam building